A Concept Analysis of Attitude toward Getting Vaccinated against Human Papillomavirus. (28th May 2013) - Ratanasiripong, Nop T.; Chai, Kathleen T.
Abstract : In the research literature, the concept of attitude has been used and presented widely. However, attitude has been inconsistently defined and measured in various terms. This paper presents a concept analysis, using the Wilsonian methods modified by Walker and Avant (2004), to define and clarify the concept of attitude in order to provide an operationalized definition for a research study on attitudes toward a behavior: getting vaccinated against HPV. While the finding is not conclusive, three attributes of attitude: belief, affection, and evaluation are described. A theoretical definition and sample cases are constructed to illustrate the concept further. Antecedents, consequences, and empirical referents are discussed. Recommendations regarding the use of the concept of attitude in research, nursing practice, and nursing education are also made.